Recent advances in low-dimensional Janus materials: theoretical and simulation perspectives. Issue 23 (4th November 2021) - Yin, Wen-Jin; Tan, Hua-Jian; Ding, Pei-Jia; Wen, Bo; Li, Xi-Bo; Teobaldi, Gilberto; Liu, Li-Min
Abstract : Owing to peculiar properties such as tunable electronic band gaps and coexistence of Rashba, excitonic and piezoelectric effects, low-dimensional Janus transition metal chalcogenides have received growing attention across different research areas. Abstract : Owing to highly peculiar properties such as tunable electronic band gaps and coexistence of Rashba, excitonic and piezoelectric effects, low-dimensional Janus transition metal chalcogenides (TMDs) have received growing attention across different research and technological areas. Experimental and theoretical investigations have shown that these emerging properties originate directly or indirectly from breaking of the mirror-asymmetry in the Janus TMD structure, resulting in an intrinsic dipole moment perpendicular to the system's layers. Despite substantial experimental and computational research in many different Janus materials and their properties, partially covered in a limited number of earlier reviews, an up-to-date comprehensive overview of the theoretical and computational advances in the field is currently lacking. To fill this gap, here we review recent theoretical and computational work on competing phases and properties of Janus TMD materials, covering their monolayers, bilayers, multilayers and hetero-structures. For each of these systems, we collate and discuss the calculated results and trends on electronic properties such as band gaps, carrier mobility, electrostatic dipole moments, ensuing work-function differences, Schottky barriers, and solar-to-hydrogen energy conversion efficiencies. Based on the computational results, we then discuss the potential of low dimensional Janus materials for a diversified set of potential applications ranging from infrared-visible photocatalytic water splitting and hydrogen evolution reactions, to gas sensing, field-effective transistors, and piezoelectric devices. We conclude the review with a critical perspective on residual theoretical, computational, and experimental challenges in the field.